Design, preparation, microstructure and properties of novel wear-resistant stainless steel-base composites using laser melting deposition. (July 2019) - Li, X.; Zhang, C.H.; Zhang, S.; Wu, C.L.; Zhang, J.B.; Chen, H.T.; Abdullah, Adil O.
Abstract: We have designed and fabricated a novel wear-resistant stainless steel-based composites using laser melting deposition (LMD) in current study. The main composition of as-deposited specimens were α-Fe, VC, Cr7 C3, and Cr23 C6 . Based on the microstructure observation and thermodynamics calculations, in situ synthesized VC particles provided sufficient places for the heterogeneous nucleation of α-Fe and chromium carbides during the solidification process of molten pool, which significantly refined the grains. The average microhardness of specimen was in range of 521 ± 9 HV - 603 ± 12 HV. The specimen with 12 wt % V content exhibited the highest wear resistance among the tested specimens as indicated by the lowest average specific wear rate of 5.011 × 10 −6  mm 3 /N m. Highlights: Novel stainless steel-base composites were fabricated using laser melting deposition. The mechanism of VC formation was analyzed based on thermodynamics. The formed VC particles led to dispersion strengthening and fine-grain strengthening. The microhardness and wear mechanism of novel stainless steel-base composites were investigated.